2010
DOI: 10.1086/657342
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 Viral Escape in Cerebrospinal Fluid of Subjects on Suppressive Antiretroviral Treatment

Abstract: Background Occasional cases of viral escape in cerebrospinal fluid (CSF) despite suppression of plasma HIV-1 RNA have been reported. We investigated CSF viral escape in subjects treated with commonly used ART regimens in relation to intrathecal immune activation and CNS penetration effectiveness (CPE) rank. Methods Sixty-nine neurologically asymptomatic subjects treated with ART >6 months and plasma HIV-1 RNA <50 copies/ml were cross-sectionally included in the analysis. ART regimens included efavirenz, lopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
222
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(245 citation statements)
references
References 28 publications
16
222
3
4
Order By: Relevance
“…[137] In some patients despite plasma viral control escape is currently unknown since it may occur in approximately 10% of patients on HAART and no neurological impairment was observed in a longitudinal study after 5 years of follow up: this event may therefore be similar to the emergence of plasma "blips". [21,138] However two case series and several case reports have clearly documented the concrete, though uncommon, possibility of symptomatic CSF escape:…”
Section: Csf Escapementioning
confidence: 99%
See 1 more Smart Citation
“…[137] In some patients despite plasma viral control escape is currently unknown since it may occur in approximately 10% of patients on HAART and no neurological impairment was observed in a longitudinal study after 5 years of follow up: this event may therefore be similar to the emergence of plasma "blips". [21,138] However two case series and several case reports have clearly documented the concrete, though uncommon, possibility of symptomatic CSF escape:…”
Section: Csf Escapementioning
confidence: 99%
“…[160][161][162][163][164][165][166][167][168][169][170][171][172] Furthermore while several retrospective studies found an association between higher CPE scores and lower CSF viral loads [153,154,[173][174][175] only one study (out of three) found a correlation with CSF escape. [21,143,176] Some reports tried to define a CPE cut off: respectively a value of 6 or 7 were found to be associated with heterogeneous CSF outcomes. [143,144,173,177] Some limitations of the CPE score must be highlighted: the limited amount of evidence regarding PD data and regarding drugs standard dosages, the absence of a clear cut off, the validation in patients receiving triple therapies and with fully sensitive viruses.…”
Section: The Cpe Scorementioning
confidence: 99%
“…Further, markers of oxidative stress, such as 4-hydroxynonenal (4-HNE), are well documented in HAND patients (Haughey, Cutler et al 2004;Sacktor, Haughey et al 2004). In addition, several studies have reported that neopterin and 2-microglobulin, regarded as indirect markers of macrophage activation, are elevated in the CSF of HIV infected patients (Yilmaz, Fuchs et al 2006;Edén, Fuchs et al 2010;Hagberg, Cinque et al 2010). Finally, the neuropathological correlates of inflammation, including astrocytosis and increased perivascular macrophage infiltration are commonly observed in the brains of HIV-infected patients (Kolson 2002;Kusdra, McGuire et al 2002;Lindl, Marks et al 2010).…”
Section: Neuropathology Of Handmentioning
confidence: 99%
“…This may be a detectable CSF viral load with undetectable plasma in a patient on stable cART, or a CSF viral load that is 5 to 10-fold higher than plasma. Patients with CSF viral escape can be symptomatic [8] or asymptomatic [17]. Reported symptoms are nonspecific and include headache, neck stiffness, confusion, and incoordination.…”
Section: Csf Viral Escapementioning
confidence: 99%